2005
DOI: 10.1097/01.ju.0000176420.83110.19
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcome of Complex Hypospadias Repairs

Abstract: Preoperative psychological counseling and discussion with other parents or patients were helpful. We no longer use free skin grafts and/or bladder mucosa for urethral substitution. Waterproofing the urethral tube was performed using either a dartos or tunica vaginalis flap. When the quality of the tissues was poor or severely scarred a 2-stage repair was performed. When resurfacing the penis local skin flaps may be insufficient or unreliable, and rotation of scrotal skin flaps or burial of the penis in the scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 16 publications
2
26
1
Order By: Relevance
“…They were motivated and gave maximum cooperation on seeing children with hypospadias who were successfully repaired, and the parents were also brought together and photographs of hypospadias before and after repair were shown to them. This was found to be very effective because the parents had to be involved in the discussion of the pathology and this increased cooperation, which was similar to the experience of earlier authors [23,24]. Unlike the initial dressing done in theatre, which was removed on the 4th postoperative day, the subsequent dressing which involved application of chloramphenicol ointment was done by the parents and this reduced stress on nursing staff.…”
Section: Discussionsupporting
confidence: 52%
“…They were motivated and gave maximum cooperation on seeing children with hypospadias who were successfully repaired, and the parents were also brought together and photographs of hypospadias before and after repair were shown to them. This was found to be very effective because the parents had to be involved in the discussion of the pathology and this increased cooperation, which was similar to the experience of earlier authors [23,24]. Unlike the initial dressing done in theatre, which was removed on the 4th postoperative day, the subsequent dressing which involved application of chloramphenicol ointment was done by the parents and this reduced stress on nursing staff.…”
Section: Discussionsupporting
confidence: 52%
“…The reoperation rate (which used as a failure rate) was 9/32 (28,125%).This reoperation rate is nearly the same as that reported by Yerkes et al [12] (29%). Higher than that of Fichtner et al [13] (24%), that of Schoreder et al [14] (22.4%), far away from that of Amukele et al [15] (12%). But it is less than that of Metro et al [16], Nelson et al [4], and Irani et al [17] those reported (50%), (51%) and (50%) respectively.…”
Section: Discussionmentioning
confidence: 40%
“…One case respond to regular dilatation leaving 2 cases (6.25%) which respond will for VIU with no case need urethroplasty. These rates is better than that of Metro et al [16] (42.8%) and that of Nelson et al [4] (14%), near to that of Fichtner et al [13] (6.1%), worse than that of Amukele et al [15] (3.6%), Schoreder et al [14] (3.5%) and that of Yerkes et al [12], Hensle et al [5] and Irani et al [17] which reported (0%) stricture urethra.…”
Section: Discussionmentioning
confidence: 46%
“…Acquired cysts are generally inclusion cysts after penile surgery such as hypospadias repair or circumcision. [64,65] Congenital cysts are usually epidermoid and typically originate from the median raphe at any level from the urethral meatus (in which case they are termed parameatal cysts, Fig. 8) [66] to the base of the scrotum.…”
Section: Review Articlementioning
confidence: 99%